The functions of еру modal verb «should» in the corpus ice-gb - R. Y. Abbasov (Vestnik MGIMO-Universiteta)
The article adresses the modal and grammatical functions of the polyfunctional verb should as presented in the language corpus ICE-GB compiled in 1993. It is based on the ideas of poly functionalism laid out in the works of A. Smirnitsky, T. Komova, and others scientists. The author aims at studying the distribution of functions of the verb should; the material is also considered from the standpoint of the extralinguistic parameters of the speaker's gender and age. The analysis of the material shows that the modal function still prevails over the grammatical one, which explains the logic of presenting the material in books on grammar where the first meaning of this verb to be studied is (mild) obligation. The grammatical function is realized in the Suppositional and Conditional oblique moods (A. Smirnitsky's classification). Genderwise, men's speech contains a few more polite formulae that show more consideration for the interlocutor which is generally considered to be typical of women's speech; on the other hand, there is some proof that phrases constructed by men are perceived as more aggressive. Bringing the speaker's age into play seems to suggest that a higher ratio of oblique moods in the speech signifies a free use of language. Some of the notional lexical verbs forming regular collocations with should have been singled out and grouped.